Isometric maximal voluntary force evaluated using an isometric mid-thigh pull differentiates English Premier League youth soccer players from a maturity-matched control group - Brownlee, T. E.; Murtagh, C. F; Naughton, R. J; Whitworth-Turner, C. M.; O'Boyle, A.; Morgans, R.; Morton, J. P.; Erskine, R. M.; Drust, B. (Science and Medicine in Football, 2018)
Purpose: The purpose of the present study was to record normative isometric maximum voluntary force (MVF) data at baseline and after an 8-week training period using the isometric mid-thigh pull (IMTP) for English Premier League academy players and a maturation-matched control group. Methods: In total, 155 English Premier League academy players across under 9 to under 21 age groups and 93, maturation-, weight- and height-matched control participants performed an IMTP. In total, 142 and 62 of the elite and control cohorts respectively were retested 8 weeks later following a period of integrated soccer training or physical education lessons. Allometrically scaled (peak force divided by body mass0.66) MVF was recorded. MVF was analysed in three maturity groups based on years from/to age of predicted peak height velocity (PHV): pre-PHV, mid-PHV, and post-PHV in elite and control groups. Results: A small difference was seen in isometric MVF in elite (115.42 ± 21.96 N) compared to control (109.36 ± 29.90 N) at baseline (P = 0.004) though no difference was seen between or within groups after 8 weeks (P > 0.167). Conclusion: Differences in baseline MVF suggest that strength is likely important to elite youth soccer performance though training undertaken by this elite group may be insufficient to elicit adaptation in isometric strength.